Temperature Behaviors of Receptor of Urban Rail Vehicle in Electrical Contact With Contact Rail - Tong Xing; Jianhua Chen; Zhiqiang Yu; Like Pan; Jianxiang Sun; An Jin; Yuehua Cui; Tao Feng; Wenxia Yan; Xudong Yi; Zimeng Zhao (IEEE Access)
Currently, many urban rail or subway vehicles obtain electrical energy through their receptors in contact with the contact rail linked to the traction network. As urban rail vehicles arrive at the station frequently or stop temporarily on the rail line, the contact rail still needs to provide the electric power for the on-board equipments. At this point, the receptor is in a static state, where the local overheating happens. This could lead to the damage of the receptor, even causing the vehicle to stop running. Based on the electrical contact theory and Fourier’s law, this paper establishes a three-dimensional thermal field finite element model for the receptor and contact rail (referred to as the boot and rail, BAR). Using the model, the change of the contact resistance under the working conditions is investigated. And the effects of the contact force, transmitted (or power supply) current and receptor wear on the temperature behaviors of the receptor are discussed. The results show that the temperature is negatively related to the contact force but closely related to the contact resistance. When the contact force is less than 100 N, the contact resistance is larger and the temperature is obviously enhanced, with the rise rate of $0.05~^{° }$ C/s. The temperature of the receptor is positively related to the transmitted current. The larger the current, the higher the temperature, more intense the temperature rise; the smaller the current, the more obvious the saturation phenomenon of the temperature, i.e. the rapid attainment of the thermal equilibrium. The larger the wear area of the BAR, the larger the convective heat flux of the receptor, leading to a lower temperature in its steady state. The innovation of this paper is to establish a three-dimensional thermal field model that can more accurately characterize the BAR system under the static electrical contact, by applying the electrical contact theory to the finite element method. Its contribution is to provide a methodology for the study of the multi-parameter three-dimensional temperature behaviors of the BAR system. And its research results present an important reference for the optimization of the receptor structure and the safe operation of urban rail vehicles.